2018
DOI: 10.5194/acp-2018-53
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and mixing state of amine-containing particles at a rural site in the Pearl River Delta, China

Abstract: Abstract. Particulate amines play an important role for the particle acidity and 43 hygroscopicity and also contribute to secondary organic aerosol mass. We investigated 44 the sources and mixing states of particulate amines using a single-particle aerosol 45 mass spectrometer (SPAMS) during summer and winter 2014 at a rural site in the 46 Pearl River Delta, China. Amine-containing particles accounted for 12.8 % and 9.2 % 47 of the total detected individual particles in summer and winter, respectively… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 36 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…The fraction of amine‐containing particles is comparable to those reported in previous studies in rural and urban areas. In a rural site in the Pearl River Delta (Heshan), amine‐containing particles accounted for 11.1% and 9.4% of the total detected individual particles in summer and winter, respectively (Cheng et al, 2018). In an urban area in southwestern China (Chongqing), 8.3% and 12.7% of the total particles were amine‐containing particles in summer and winter, respectively (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fraction of amine‐containing particles is comparable to those reported in previous studies in rural and urban areas. In a rural site in the Pearl River Delta (Heshan), amine‐containing particles accounted for 11.1% and 9.4% of the total detected individual particles in summer and winter, respectively (Cheng et al, 2018). In an urban area in southwestern China (Chongqing), 8.3% and 12.7% of the total particles were amine‐containing particles in summer and winter, respectively (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The TMA‐containing particles peaked at 0.5 to 0.6 μm on clear days and shifted to larger sizes with a peak at 0.6 μm during fog events (Zhang et al, 2012). Cheng et al (2018) reported that amine‐containing particles peaked in the size range of 0.5 to 0.7 μm in both summer and winter. In southwestern China, DEA‐containing particles were reported to peak at 0.6 μm (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Amines are widely present in rainwater, fog, gas and particle phases ( Ge et al, 2011b ), and they can be emitted from a variety of natural (e.g., marine environment and vegetation) and anthropogenic (e.g., biomass burning, animal husbandry, vehicle exhaust, and industrial processes) sources ( Ge et al, 2011a ; Murphy et al, 2007 ). Laboratory experiments and theoretical calculations have demonstrated that amines are more alkaline than ammonia, although the gaseous concentration of amine is one or two orders of magnitude lower than ammonia ( Cheng et al, 2018 ; Ge et al, 2011a ; Sorooshian et al, 2008 ). The concentration of amines is only 14%–23 % of ammonium, but it has been thought to be a key basic compound even in aerosol particles containing ammonium ( Sorooshian et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, single particle aerosol mass spectrometer (SPAMS) and aerosol time-of-flight mass spectrometry (ATOFMS) have been widely employed to study the chemical compositions, mixing states, and formation processes of amine-containing particles at a high time resolution ( Chen et al, 2019 ; Cheng et al, 2018 ; Healy et al, 2015 ; Lian et al, 2020b ; Qin et al, 2012 ). The gas-to-particle partitioning of amine is influenced by many factors, such as aerosol liquid water content (ALWC), particulate acidity, and atmospheric oxidation capacity, as well as meteorological conditions including relative humidity (RH) and temperature ( Chen et al, 2019 ; Cheng et al, 2018 ). Previous studies in southern China found that high RH condition was favorable for the enhancement of amine-containing particles ( Chen et al, 2019 ; Cheng et al, 2018 ; Zhang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation